Evaluation of Acetylcholinesterase Inhibitory Activity of Fractions from Mahonia nepalensis (Berberidaceae) Extract - Tung, Bui Thanh; Son, Phan Ke; Thu, Dang Kim; Hai, Nguyen Thanh; Bach, Nguyen Xuan; Thu, Nguyen Thi Kim (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 33 No 2, 2017)
Acetylcholinesterase (AChE) is a key target in the treatment of Alzheimer’s disease. Principal role of AChE hydrolyzes the neurotransmiter acetylcholine. Medicinal plants are the potential source of AChE inhibitors. In this study, we studied the AChE inhibitory activities of extraction  Mahonia nepalensis . This medicianl plant was extracted with ethanol 96% and subsequently fractionated with n-hexane, ethyl acetate (EtOA) and n-butanol (n-BuOH) solvents. These fractions were evaluated the AChE inhibitory activity by Ellman’s colorimetric method.  Results showed that n-BuOH fraction had the strongest AChE inhibitory activity, followed by EtOH extract and the EtOAc fraction was the weakest. The n-BuOH fraction inhibited AChE activity in a dose-dependent manner with an IC 50 value of 3.38 ± 0.07 μg/mL. Detailed kinetic analysis indicated that n-BuOH fraction was mixed inhibiton type with Ki value of 3.416 ± 0.05 µg/mL. Our  data suggests that  the  Mahonia nepalensis may be  a  promising  source  of  AChE  inhibitors  for Alzheimer’s disease.